2016
DOI: 10.1155/2016/6437585
|View full text |Cite
|
Sign up to set email alerts
|

Sex Hormone Binding Globulin Modifies Testosterone Action and Metabolism in Prostate Cancer Cells

Abstract: Sex Hormone Binding Globulin (SHBG) is the major serum carrier of sex hormones. However, growing evidence suggests that SHBG is internalised and plays a role in regulating intracellular hormone action. This study was to determine whether SHBG plays a role in testosterone uptake, metabolism, and action in the androgen sensitive LNCaP prostate cancer cell line. Internalisation of SHBG and testosterone, the effects of SHBG on testosterone uptake, metabolism, regulation of androgen responsive genes, and cell growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 34 publications
(38 reference statements)
1
31
0
1
Order By: Relevance
“…In addition, a single nucleotide polymorphism related to an elevated plasma SHBG concentration reportedly correlates with a reduced risk of diabetes [ 13 ]. The hormone-like effect of SHBG has also been demonstrated in experiments using prostatic cells [ 14 , 15 ], MCF-7 breast cancer cells [ 16 ], cytotrophoblasts [ 17 ], proximal tubule epithelial cells [ 18 , 19 ], and hepatocytes [ 12 ]. The results of these previous studies led us to speculate that the serum SHBG level is not only simply a consequence of altered metabolic conditions but also exerts favorable effects protecting against the development of metabolic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a single nucleotide polymorphism related to an elevated plasma SHBG concentration reportedly correlates with a reduced risk of diabetes [ 13 ]. The hormone-like effect of SHBG has also been demonstrated in experiments using prostatic cells [ 14 , 15 ], MCF-7 breast cancer cells [ 16 ], cytotrophoblasts [ 17 ], proximal tubule epithelial cells [ 18 , 19 ], and hepatocytes [ 12 ]. The results of these previous studies led us to speculate that the serum SHBG level is not only simply a consequence of altered metabolic conditions but also exerts favorable effects protecting against the development of metabolic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…30 An in vitro study, demonstrated that SHBG decreased excretion of testosterone from the body and enhanced the effect of testosterone on the androgen responsive genes. 31 We found low SHBG and testosterone in men with SCH/hypothyroidism, which is a well-recognised feature in hypothyroid patients and it has been observed that these levels return to normal levels with replacement of THs. 8,32 The spermogram and reproductive hormones were reduced in subjects who had anti TPO antibodies >35 IU/mL.…”
Section: Discussionmentioning
confidence: 50%
“…Cells were then fixed by 2% ( v/v ) paraformaldehyde in PBS (pH 7.3) for 5 min at RT. The fixed cells were washed with PBS and then permeabilized by 0.2% ( v/v ) Triton X-100 in PBS for 15 min [ 41 ] followed by washing with PBS and then permeabilized by 0.2% Triton X-100 in PBS for 15 min [ 41 ]. Cells were blocked with Protein Blocking Reagent (DAKO) for 20 min and then incubated with a mixture of two primary antibodies containing equal amounts (100 μL) of mouse anti-SjTPI serum diluted 1:50 in 2% BSA-PBS (pH 7.3) and 100 μL of rabbit anti-Actin antibody (1:75 diluted in 2% BSA-PBS) (Invitrogen) for 2 h at RT.…”
Section: Methodsmentioning
confidence: 99%